Association between the presence of antibodies against Leptospira and kidney lesions in cattle - Burgos Macías, Daniel Isaías (2020)
The aim of this study was to determine the possible relationship between the presence of lesions called “White Spotted Kidney” (WSK) and the seroprevalence of Leptospira spp in cattle slaughtered in the Manta slaughterhouse, Manabí province, Ecuador. Blood samples were taken from 320 cattle to detect antibodies against Leptospira spp using the microagglutination technique. Likewise, a macroscopic revision of the kidneys was made, and samples were taken for histopathological analysis. The seroprevalence of Leptospira spp was 50.9% and the frequency of kidney injury was 18.13%. The presence of the eight serovars evaluated was found, with the serovars Pomona, Icterohaemorragiae and Bratislava being the most frequent. Animals serologically positive for Leptospira are 40.56 more likely to have specific lesions associated with the disease at the time of slaughter (p<0.00001; OR = 40.56; 95% CI = 9.86-169.79). A significant association was found between the presence of kidney lesions with the serovars Icterohaemorragiae, Canicola, Hardjo and Wolffi. No association was found between the presence of lesions with the sex of the animals or with the canton of origin. It is concluded that there is a relationship between seroprevalence to Leptospira spp and the presence of kidney lesions (WSK).